Cultural Immersion in the Digital Age: Developing "Chinese Cultural Wonders" Virtual Tour for Cross-Cultural Understanding - Dwi Ayu Shofiana; Lukluk Ul Muyassaroh; Primardiana Hermilia Wijayati; Dhevy Olivia Firdaus (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This study aims to develop Virtual Tour-based learning media entitled Chinese Cultural Wonders to improve cross-cultural understanding of China in a contextual and interactive manner for students of the Chinese Language Education S1 Study Program at Universitas Negeri Malang. This research uses the research and development (R&D) method with the ID-TABLET Culture-Based Model (CBM) which consists of pre-production, production, and post-production stages. The media was developed through 360-degree panoramic recording at Tjoe Hwie Kiong Temple, integration of interactive multimedia, and preparation of Chinese culture-based teaching materials that were visually packaged through the Canva platform. The prototype was validated by material experts and media experts and tested on students of the Chinese Language Education study program class of 2023. Chinese Cultural Wonders is a Virtual Tour-based application that can be accessed online. This application consists of the main menu in the form of material content, quizzes, usage guides, mini-maps, temple locations, and contact information. In addition, this application is also equipped with pop-up images, pop-up videos, and navigation hotspots that can increase user interactivity in using it.